2024
DOI: 10.3390/en17051234
|View full text |Cite
|
Sign up to set email alerts
|

A Diagnostic Curve for Online Fault Detection in AC Drives

Natalia Koteleva,
Nikolai Korolev

Abstract: The AC drive is an important component and the most common element of any manufacturing process. A particularly serious task is the proper assessment of the AC drive’s technical condition, as its failure can cause problems for entire units and complexes of industrial enterprises. At present, there are several approaches either to determine electric drives’ condition or to find certain defects. Frequently, these methods require the installation of additional equipment that exceeds the price of the electric driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The integration of diagnostic tools and algorithms into mine hoisting systems provides a comprehensive approach to maintenance [12,13]. A good solution in this case is the use of machine learning algorithms to recognise patterns and predict potential problems [14,15]. Testability is a property that characterises the adaptability of an object to technical diagnostics, allowing for its condition to be determined reliably with minimum costs.…”
Section: Introductionmentioning
confidence: 99%
“…The integration of diagnostic tools and algorithms into mine hoisting systems provides a comprehensive approach to maintenance [12,13]. A good solution in this case is the use of machine learning algorithms to recognise patterns and predict potential problems [14,15]. Testability is a property that characterises the adaptability of an object to technical diagnostics, allowing for its condition to be determined reliably with minimum costs.…”
Section: Introductionmentioning
confidence: 99%
“…The real power consumption for lifting a unit of payload differs from the standardized one, which, naturally, causes changes in the parameters of cargo flows. The authors in [12][13][14] investigated the reliability of mining machines and showed that the use of new technologies and materials helped to increase the service life and efficiency of the equipment. They identified the main problem nodes and proposed innovative solutions to improve the reliability and safety of mining machines [15].…”
Section: Introductionmentioning
confidence: 99%